Confronting finance : mobilizing the 99 per cent for economic and social progress - Pons-Vignon, Nicolas; Ncube, Phumzile (ILO, 2012)
The unfolding economic crisis has unequivocally proved that neoliberal policies were no better for growth than for social progress. As poverty and inequality are rising to alarming levels in Europe, the old continent seems at a loss to respond. Political leaders seem content to liquidate the social gains made by workers' struggles. A small minority, possibly even smaller than 1 per cent, associated with the financial sector, stands to benefit from a deepening of neoliberalism.